Children's conservation ability in Quezon City as related to age and socio-economic class with implications for mathematics education - Casareo, Divina E. 1937- ([Quezon City s.n.], 1973)
The influence of age, experience, socioeconomic class and language with implications for mathematics education was examined in this paper.
Thesis (M.A.T. Elementary Mathematics)--University of the Philippines.
Keywords: Cognition; Child study